Prevalence and risk factors of adverse birth outcomes in the Pacific Island region: A scoping review - Lydia S.K. Kaforau; Gizachew A Tessema; Jonine Jancey; Gursimran Dhamrait; Hugo Bugoro; Gavin Pereira (Elsevier, 2022)
Summary: Background: Prevalence and exposures of adverse birth outcomes is well studied in low-and-middle-income countries but not well-established for the Pacific Island region. Our study mapped the available evidence on low birth weight (LBW), preterm birth, and small for gestational age (SGA)'s prevalence and their corresponding risks in the region. Methods: We followed the five-staged Arksey and O'Malley's framework with clinicians' consultation in the region. Five scholarly databases and non-indexed studies were searched and extracted data were analysed as numerical and thematic summaries mapping the outcomes and exposures. Findings: We included 20 studies representing 11 Pacific Island countries with the following mean prevalence and associations at 95% confidence interval. Estimated mean prevalence for LBW and preterm births were 12% and 13%, respectively. LBW were associated with malaria in pregnancy [aOR 3.3 (1.00, 10.60)], and betel nut and tobacco [aOR 2.4 (1.00, 6.00)]. Preterm births were associated with malaria in pregnancy [aOR 6.6 (2.46, 17.62)] and maternal obesity [aOR 1.5 (1.00, 2.30)]. SGA were associated with short stature [aOR 1.7 (1.22, 2.41)] and no antenatal bookings [aOR 4.0 (2.12, 7.57)] Interpretation: Several significant factors identified were malaria infection, obesity, betel nut and tobacco and no antenatal care, also validated by clinicians consulted. Funding: Australia National Health and Medical Research Council.